Determining Factors and Zootechnical Output of Biosecurity Practices in Fish Farms in the Wouri Division, Cameroon - Fonkwa Georges; Makombu Judith Georgette; Kamdem Alex Henri; Kametieu Djamou Franck; Nack Jacques; Awah-Ndukum Julius; Tomedi Eyango Minette; Tchoumboue Joseph (Veterinary Medicine International)
Biosecurity practice limits the occurrence of diseases and economic losses in fish farms. The objective of this study was to characterize fish farming in the Administrative Division of Wouri, Cameroon (3°97′04″–3°58′13″N; 9°76′78″–9°46′4.3″E) and assess the biosecurity practices. A cross-sectional biosecurity audit was then conducted in 33 fish farms from March to May 2022. The “snow ball” technique, on-farm observations, and face-to-face interviews of farm managers using a semistructured questionnaire were used for data collection. The results showed that most of the fish farmers were between 18 and 40 years of age (63.64%) and not trained in fish farming (60.61%). The lack of finance (57.57%) was the main constraint to the biosecurity practice. The high fish mortality rate (>15%) was recorded in 66% of the farms. Overall, the compliance rate (CR = 40.52 ± 14.70%) and adoption rate (AR = 40.40 ± 30.10%) of biosecurity measures were intermediate. No type C farm or at the minor risk level of contamination was recorded. Farmers of 18 to 40 years of age (45.24 ± 14.75%) who attended higher school (43.83 ± 14.44%) and received training in fish farming (47.44 ± 14.39%) recorded a significant higher CR. The CR and AR were significantly higher for the isolation component (CR = 60.17 ± 19.81%; AR = 60.17 ± 25.68%) followed by traffic control (CR = 53.53 ± 25.87%; AR = 53.53% ± 34.86) and sanitation (CR = 27.70 ± 19.70%; AR = 29.84 ± 26.00%). A strong (R2 = 0.725), positive, and significant (p=0.019) linear relationship was found between the level of education of fish farmers and the biosecurity compliance rate while the health status of fish was weakly (R2 = 0.207), positively, and significantly (p=0.017) influenced by the compliance rate. Fish farming is an income-generating activity that still requires socioeconomic, technical, and institutional efforts for optimal productivity. The Cameroonian government should emphasize on the education, training, and capacity building of farmers on biosecurity practices to minimise the introduction, establishment, and spread of diseases.